The Large Cutting Tools from Wonderboom, South Africa. (3rd April 2022) - Lotter, Matt G.; Caruana, Matthew V.; Lombard, Marlize
ABSTRACT: Wonderboom remains largely excluded from discussions about the Earlier Stone Age of southern Africa, despite having one of the largest Acheulean assemblages for the region. With this contribution, we revisit its large cutting tool assemblage (namely the handaxes, cleavers, picks and knives) and investigate some of the tool manufacturing preferences of the hominins who used the site during the Earlier Stone Age. We also provide an inter-site comparison of handaxes with another later and two early Acheulean sites from South Africa, wherein the Wonderboom assemblage clusters with the later Acheulean and is distinguished from the early Acheulean assemblages. This tentatively places Wonderboom within the South African Acheulean chronology and provides the first characterization of later Acheulean LCT production strategies for the region that includes the Cradle of Humankind.